P-136 Enabling quality of life by a rehabilitative approach of adding life to days. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Wright, Lisa
Abstract : Utilising a grant awarded by St James's Place Charitable Foundation we have created a culture of rehabilitation, enabling true patient-centred care in order to work towards the benchmark for best practice as set out in the 'How rehabilitative is your hospice' guidance by Hospice UK. A hospice wide approach has been adopted in order to facilitate and establish a culture shift across support and therapy day services and the hospice's in-patient unit with wider effects tangible across the organisation. A wide range of disease specific self-management groups have been created with full MDT involvement, goal setting has been a key focus and patient passports to assist with self-management of symptoms have been created. Goal setting in order to achieve a rehabilitative and enabling approach has been the main focus within the inpatient unit and has required a culture shift away from disabling patients with our approach to care and having a much more individualised goal-focused approach to the whole multidisciplinary team delivery of care. Outcomes have been measured by observing changes in Patient Outcome Scores and sometimes Karnofsky scores together with successful achievement of individual goals and feedback from patients. This approach has supported the 292 attendance within the in-patient unit from 1 April 2017 to 31 March 2018. A review of the training sessions undertaken across all internal staff members, trustees and volunteers has identified approximately 150 indirect beneficiaries. The creation of a team of enabling volunteers has helped to discover what really matters to patients across all hospice services. By using one-page profiles we are establishing personal activities, goals and areas that patients wish to participate in or talk over. These activities have relevance and meaning giving them a sense of purpose to exist and enabling them to live until they die.